2018
DOI: 10.1016/j.amsu.2018.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Association between Q192R polymorphism in the PON1 gene and statin responses in cardiac patients

Abstract: IntroductionParaoxonases are a group of different forms enzymes that consist of three non-similar isoforms, PON1, PON2 and PON3, which are located near to each other on the long arm of chromosome7. This study aims to investigate the association of a Q192R polymorphism of PON1 gene and statin response in patients with ischemic heart disease with dyslipidemia.MethodsThe studied population included three hundred patients with coronary artery disease with dyslipidemia who were prescribed statins. Total lipid profi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…64 The importance of this PON1 coding polymorphism has also been demonstrated in findings by Abd Elgwad and coworkers, which estimated the response of the HDLcholesterol concentration to statin therapy. 65 They found that Q allele carriers responded better to statin therapy with respect to increased HDL-cholesterol concentration, than RR homozygotes. This opens a new area of potential drug design studies related to statin therapy clinical usefulness.…”
Section: Pon1 and Vascular Diseasesmentioning
confidence: 99%
“…64 The importance of this PON1 coding polymorphism has also been demonstrated in findings by Abd Elgwad and coworkers, which estimated the response of the HDLcholesterol concentration to statin therapy. 65 They found that Q allele carriers responded better to statin therapy with respect to increased HDL-cholesterol concentration, than RR homozygotes. This opens a new area of potential drug design studies related to statin therapy clinical usefulness.…”
Section: Pon1 and Vascular Diseasesmentioning
confidence: 99%
“…Many studies evaluating how different statins influence PON1 activity are provided [32,33,34], a recently published meta-analysis [35] confirms, independent of particular drug, dose, treatment duration and serum lipid profile, an effect of enhancing PON1 activities and concentration. Additionally, it is described that individual response to treatment with statins is dependent on PON1 Q192R polymorphism [36], which may explain the significant difference of PON1 paraoxonase activity between patients with and without treatment noted in our study.…”
Section: Discussionmentioning
confidence: 66%
“…[22] One prospective and one crosssectional studies for patients with Q allele of the PON1 Q192R polymorphism HDL-C goals were attained moreover than patients with RR homozygosity. [23,24] In Japanese, diabetic patient with Q allele who was treated with…”
Section: Pon1 Genementioning
confidence: 99%
“…Ciuculete et al (2017) [19] Prospective Four SNPs within the APOE cluster (rs7412, rs4420638), ABCC2 (rs2002042) and CELSR/SORT1/PSRC1 (rs646776), displayed a major impact on statin efficacy. Elgwad et al (2018) [23] Prospective Q192R polymorphism of PON1gene had important role in interindividual variety in accomplishment of HDL-C goals in response to statins. Sumi et al (2017) [24] Cross-sectional PON1 Q192R polymorphism who were treated with statins exhibited improvement in glucose metabolism.…”
Section: Article Title Study Design Conclusionmentioning
confidence: 99%
See 1 more Smart Citation